Transparent Exopolymer Particle (TEP) distribution and in situ prokaryotic generation across the deep Mediterranean Sea and nearby North East Atlantic Ocean - Ortega-Retuerta, E. (Eva); Mazuecos, I.P.; Montero, M.F.; Reche, I. (Isabel); Gasol, J.M. (Josep María); Álvarez, M. (Marta); Álvarez-Salgado, X.A. (Xosé Antón); Arístegui, J. (Progress in Oceanography, 2019)
Transparent exopolymer particles (TEP) play a key role in ocean carbon export and structuring microbial habitats, but information on their distribution across different ocean basins and depths is scarce, particularly in the dark ocean. We measured TEP vertical distribution from the surface to bathypelagic waters in an east-to-west transect across the Mediterranean Sea (MedSea) and the adjacent North Eastern Atlantic Ocean (NEA), and explore their physical and biological drivers. TEP ranged from 0.6 to 81.7µg XG eq L −1 , with the highest values in epipelagic waters above the deep chlorophyll maximum, and in areas near the Gibraltar and Sicily Straits. TEP were significantly related to particulate organic carbon (POC) in all basins and depth layers (epipelagic vs. deep), but the contribution of TEP to POC was higher in the NEA (85%, 79% and 67% in epi-, meso- and bathypelagic waters, respectively) than in the MedSea (from 53% to 62% in epipelagic waters, and from 45% to 48% in meso- and bathypelagic waters), coinciding with higher carbon to nitrogen particulate organic matter ratios in the NEA. The TEP connectivity between epipelagic waters and mesopelagic waters was less straightforward than between mesopelagic waters and bathypelagic waters, with a 23% and 55% of the variance in the relationship between layers explained respectively. Prokaryotes were found to be a likely net source of TEP as inferred by the significant direct relationship observed between prokaryotic heterotrophic abundance and TEP. This assumption was confirmed using experimental incubations, where prokaryotes produced TEP in concentrations ranging from 0.7 (Western Mediterranean, bathypelagic) to 232 (Western Mediterranean, mesopelagic) µg XG eq. L −1 day−1